STUDENTS’ READINESS AND ATTITUDES ON BLENDED LEARNING: BASIS FOR THE DEVELOPMENT OF A FLIPPED-CLASSROOM LANGUAGE MATERIAL - Eustaquio, Ma. Theresa; Gannaban, Genalyn (International Journal of Arts, Sciences and Education, 2024)
This paper investigates students' attitudes and readiness for blended learning. It explores how prepared students are for this kind of learning as well as how they feel about language learning that takes place in flipped classrooms. It employed descriptive quantitative research design and based on the results, the respondents have positive attitudes on blended learning finding it flexible and engaging, and they are already ready to this new kind of teaching-learning environment. Thus, these students are generally familiar with and at ease with the required technology tools and platforms, indicating a moderate to high degree of preparation for blended learning. This positive attitudes and preparedness provide a strong basis for the creation of customized language resources that maximize blended learning's advantages.